PEl'lGEMBANGAN INTELLECTUAL CAPITAL DAN SOCIAL CAPITAL MELALUI PENDIDIKAN KEWARGANEGARAAN - Suyato Suyato (LPMPP Universitas Negeri Yogyakarta, 2007)
Developingintellectu,,1 and social capital in preparing student for their future'srole as constructiveand critical citizen is essential in a healthy de ocratic state,School-based civiceducation ,as one of means in building such ones faces somechallenges, Developing intellectual and capital, may be, is the greatest one. Thispaper tries to propose the urgency of such effort by arguing that school